Method for detecting mechanical properties of open-cell foam-based interpenetrating phase composite material

Through refined modeling and finite element analysis, the accuracy and efficiency of mechanical properties detection of open-cell foam-based interpenetrating composite materials are solved, and fast and accurate mechanical properties detection is achieved, reducing costs and test piece damage is achieved. risk.

CN119230030AActive Publication Date: 2024-12-31NAT UNIV OF DEFENSE TECH

Patent Information

Application Number
CN202411384922.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-31
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The prior art is difficult to accurately and quickly detect the mechanical properties of open-cell foam-based interpenetrating composite materials, and the experimental methods are time-consuming and cost-effective, and may cause damage to the specimens, affecting the accuracy of design and production.

Method used

Using a refined model modeling method, the mechanical performance detection is carried out through the combination of random porous model and fill phase model, combined with finite element analysis software, and the open-cell foam-based interpenetrating phase composite material model is established for application scenarios, and dynamic analysis is carried out. Obtain mechanical properties characterization parameters.

Benefits of technology

Accurate detection of the mechanical properties of open-cell foam-based interpenetrating composite materials is achieved, saving time and cost, avoiding specimen damage, and improving the accuracy and efficiency of design and production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230030A_ABST
    Figure CN119230030A_ABST
Patent Text Reader

Abstract

The invention discloses a method for detecting mechanical properties of an open-cell foam-based interpenetrating phase composite material, and aims to solve the problems of complexity, inconvenience, high time cost and high economic cost of the conventional detection method. According to the technical scheme, the method comprises the following steps: firstly, establishing an open-cell foam-based interpenetrating phase composite material model formed by filling an open-cell foam material matrix with a filling phase model according to an application scene; finite element analysis software is adopted for conducting finite element analysis on the model, and mechanical property characterization parameters of the model are obtained. And comparing the mechanical property characterization parameters of the model with the mechanical property characterization parameters required by the application environment, and detecting whether the mechanical property characterization parameters of the model meet the requirements of the application environment so as to judge whether to design the open-cell foam-based interpenetrating phase composite material according to the model. By adopting the method, the open-cell foam-based interpenetrating phase composite material does not need to be really prepared, the mechanical property of the open-cell foam-based interpenetrating phase composite material can be accurately detected in real time, the cost is low, and the professional ability requirement is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of mechanical property testing of interpenetrating phase composite materials, and in particular to a method for testing the mechanical properties of an open-cell foam-based interpenetrating phase composite material. Background Art

[0002] The protective structures of key components (such as engines and their key components, power systems, electronic equipment, etc.) in the fields of aviation, aerospace, and shipbuilding are generally made of a single material (i.e., steel, aluminum, etc.). The single material has a simple structure, poor corrosion resistance and heat resistance, and cannot meet its special requirements in a specific environment. The open-cell foam-based interpenetrating composite material can make up for the shortcomings of a single material. In actual engineering, there is an increasing need for some dual-property materials that are lightweight, high-strength, high-toughness, and have certain functions. The open-cell foam-based interpenetrating composite material has broad application prospects in the fields of aviation, aerospace, transportation, energy, and construction. The open-cell foam-based interpenetrating composite material is a multiphase material with topological continuity, interconnectivity, and isotropy. It exhibits unique mechanical properties (such as excellent impact resistance, good heat resistance and corrosion resistance, adjustable thermal expansion coefficient, excellent fatigue life, etc.). These properties are superior to traditional composite materials that are simply combined by different materials. The open-cell foam-based interpenetrating composite material will synergistically contribute its own characteristics to the multifunctionality of the entire material at every stage of application. For example, if one component of the open-cell foam-based interpenetrating composite material provides toughness and strength, then another component may provide thermal stability, wear resistance, shock resistance or damping performance. It can be said that the two components are two separate parts in space, and each of them runs through the entire interpenetrating composite material in the spatial dimension. Since the components of the open-cell foam-based interpenetrating composite material are interconnected in three-dimensional space and entangled in all directions, the interface volume ratio is quite high, so it can meet certain mechanical properties and have certain functionality.

[0003] In the design and manufacturing process of open-cell foam-based interpenetrating composite materials, experiments are generally used to determine whether the designed and produced open-cell foam-based interpenetrating composite materials meet the requirements of mechanical properties in practical applications (i.e., toughness, strength, etc., characterized by mechanical property characterization parameters such as yield strength σ, failure stress Q, elastic modulus E, and energy absorption parameter D). However, the microstructure of open-cell foam-based interpenetrating composite materials is complex, and the preparation process is complex. Testing the mechanical properties of open-cell foam-based interpenetrating composite materials is a challenge. To test the mechanical properties of open-cell foam-based interpenetrating composite materials by experimental means, it is first necessary to prepare open-cell foam-based interpenetrating composite materials. The internal structure of open-cell foam-based interpenetrating composite materials is complex, the preparation process is complex, the preparation time is long, the preparation process is prone to errors, and the scrap rate is high. At the same time, universal testing machines, Hopkinson pressure bars and other testing equipment are required to experimentally test the mechanical properties of open-cell foam-based interpenetrating composite materials. The testing process has high professional requirements for testing equipment and testers, and may cause damage to the material specimens to be tested. Therefore, it is inconvenient and expensive to test the mechanical properties of open-cell foam-based interpenetrating phase composites using experimental methods, and both the time cost and the economic cost are high.

[0004] Therefore, the use of numerical simulation to detect the dynamic mechanical behavior of open-cell foam-based interpenetrating phase composites has become an increasingly important means of detecting whether open-cell foam-based interpenetrating phase composites meet application requirements. The method of using numerical simulation to detect the mechanical properties of open-cell foam-based interpenetrating phase composites mainly includes the following steps:

[0005] The first step is to build an open-cell foam-based interpenetrating composite model, which includes the following steps:

[0006] 1.1 Construct a random porous model;

[0007] Open-cell foam-based interpenetrating phase composite materials are composed of random porous models and filling phase models. Random porous models are divided into the following three types: (1) Regular geometric models, such as Gibson-Ashby model, Kelvin model, and cubic cavity model. Regular geometric models are composed of multiple identical cells arranged in order in space. The shape and size of the cells are highly controllable. Therefore, the modeling process of regular geometric models is simple, the cell structure is single, and it is not random, which is quite different from the real foam structure. (2) 3D tomography reconstruction model. This modeling method is a true reproduction of the cell structure of the foam material, and can even reconstruct small holes, cracks and other defects inside the material. However, since 3D tomography requires high-precision scanning equipment, complex image processing algorithms, and a large amount of post-data processing by professionals, the time and labor costs are high, and the generated model cannot be directly used for finite element calculations. The overly fine parts of the model are difficult to divide into grids, and the model needs to be idealized using graphics processing software. The entire process is very complicated. (3) Random evolution model. The most widely used is the Voronoi model. This modeling method divides the space into a series of polygonal areas, each of which contains a discrete point (called a "seed point"). Foam materials with different structures can be generated by controlling the number of seed points, the minimum distance between seed points, and the wall thickness. It has strong designability, but its disadvantage is that it can only more realistically reflect the closed-cell foam structure with a relatively low density. Moreover, since the cell wall is relatively thin relative to the cell hole, the generated model can often only use shell units to divide the grid, making the finite element simulation calculation inaccurate.

[0008] 1.2 Construct filling phase model;

[0009] Filling phase materials are filled into the pores of the random porous model so that the pores of the random porous model are completely filled with filling phase materials. The filling phase materials in all pores constitute a whole, which is called a filling phase model. The random porous model and the filling phase model together constitute an open-cell foam-based interpenetrating composite material model. Taking the model software Rhino as an example, the specific operation is: construct a filling phase model that is consistent with the external shape and geometric dimensions of the random porous model, overlap the random porous model with the filling phase model on the external contour, remove the overlapping part of the filling phase model with the random porous model, and then combine the random porous model with the filling phase model remaining after removing the overlapping part to generate an open-cell foam-based interpenetrating composite material model.

[0010] The second step is to perform finite element analysis on the open-cell foam-based interpenetrating phase composite material model to obtain the mechanical properties characterization parameters of the open-cell foam-based interpenetrating phase composite material model (mainly including yield strength σ, failure stress Q, elastic modulus E, and energy absorption parameter D);

[0011] In the third step, the mechanical property characterization parameters of the open-cell foam-based interpenetrating composite material model obtained in the second step through the finite element analysis process, namely, yield strength σ, failure stress Q, elastic modulus E, and energy absorption parameter D, are compared with the mechanical property characterization parameters of the application environment requirements, namely, yield strength σ0, failure stress Q0, elastic modulus E0, and energy absorption parameter D0, to detect whether the mechanical property characterization parameters of the open-cell foam-based interpenetrating composite material model meet the application environment requirements. If the yield strength σ, failure stress Q, elastic modulus E, and energy absorption parameter D of the open-cell foam-based interpenetrating composite material model all meet the application requirements, it means that the yield strength σ, failure stress Q, elastic modulus E, and energy absorption parameter D of the open-cell foam-based interpenetrating composite material model are qualified; if any one of the yield strength σ, failure stress Q, elastic modulus E, and energy absorption parameter D of the open-cell foam-based interpenetrating composite material model does not meet the application requirements, it means that the open-cell foam-based interpenetrating composite material model does not meet the mechanical property requirements of the application environment, and the open-cell foam-based interpenetrating composite material model should be adjusted, and the open-cell foam-based interpenetrating composite material should be designed according to the open-cell foam-based interpenetrating composite material model that meets the mechanical property requirements of the application environment.

[0012] In engineering applications, since the model established in the first step has a lot of simplifications or defects compared to the real model, the mechanical property characterization parameters such as yield strength σ, failure stress Q, elastic modulus E, and energy absorption parameter D of the open-cell foam-based interpenetrating phase composite material are calculated by numerical simulation, which makes the calculation of the mechanical property characterization parameters inaccurate. In the third step, misjudgment occurs when the mechanical property characterization parameters of the open-cell foam-based interpenetrating phase composite material model are detected, and it is impossible to provide real-time and accurate guidance for design and production, which affects the design, optimization and use of the open-cell foam-based interpenetrating phase composite material, resulting in premature damage to the protection, vibration isolation and other structures of key components in the fields of aviation, aerospace, and automobiles, causing immeasurable losses. Summary of the invention

[0013] The technical problem to be solved by the present invention is to propose a method for testing the mechanical properties of open-cell foam-based interpenetrating phase composite materials, so that the mechanical properties test of the open-cell foam-based interpenetrating phase composite materials is accurate, time is saved, and no damage is caused to the material specimens to be tested, thereby being able to guide the design and production of the open-cell foam-based interpenetrating phase composite materials in real time and accurately, realizing the rapid design, optimization and use of the open-cell foam-based interpenetrating phase composite materials, and saving design production and manufacturing costs.

[0014] In order to achieve the above purpose, the following technical solutions are adopted:

[0015] The first step is to establish an open-cell foam-based interpenetrating composite material model. The refined modeling process of the open-cell foam-based interpenetrating composite material model is:

[0016] 1.1 According to the application scenario (such as protection of engines and their key components, power systems, electronic equipment, etc.), the shape and size of the open-cell foam-based interpenetrating composite material model are determined. The maximum area of ​​the open-cell foam-based interpenetrating composite material model is greater than or equal to the area of ​​the maximum surface of the protected electronic components. Let the volume of the open-cell foam-based interpenetrating composite material model determined according to the application scenario be V m .

[0017] 1.2 According to the open-cell foam-based interpenetrating composite material model, the volume of the random porous model is determined as V0 and the average number of pores N of the random porous model, and seed points are randomly arranged in the random porous model. The method is:

[0018] The geometric shape of the random porous model is determined as a cuboid, and the volume of the random porous model is defined as V0. The random porous model is required to fully accommodate at least two open-cell foam-based interpenetrating composite material models determined according to the application scenario, that is, V0≥2V m According to the application scenario, the average number of open cells per inch (ppi) of the open-cell foam matrix is ​​determined (generally ppi is 20 to 100), and the average number of holes N in the random porous model is determined by formula (1):

[0019]

[0020] 1.3 Determine the number of seed points M of the 3D-Voronoi model by the average number of holes N in the random porous model, that is, let M = N. (The 3D-Voronoi model is a 3D discretization method based on the Voronoi diagram. It divides the three-dimensional space into a series of polyhedral units, each of which contains a discrete point (called a "seed point"). Foam materials with different structures can be generated by controlling the number of seed points M, the minimum distance between seed points, and the wall thickness of the polyhedral unit.

[0021] 1.4 Randomly arrange M seed points in the random porous model to fill the entire random porous model.

[0022] 1.5 A 3D-Voronoi model is established based on randomly arranged seed points in the random porous model, and a 3D-Voronoi cell is generated from the 3D-Voronoi model.

[0023] There is a space near the randomly distributed seed points in the random porous model, which is called the Voronoi unit. The distance from any point A in the Voronoi unit (any point except the seed point) to the seed point Q in the Voronoi unit is smaller than the distance from point A to other seed points in the space (other seed points except point Q), that is, each Voronoi unit only encloses one seed point. A 3D-Voronoi model is constructed by all Voronoi units in the random porous model. Through the 3D-Voronoi model, a series of 3D-Voronoi cells can be obtained. Each 3D-Voronoi cell corresponds to a seed point in the random porous model and has different geometric shapes and sizes.

[0024] 1.6 Extract the points and lines of the 3D-Voronoi cells and generate the structural line model by:

[0025] 1.6.1 Decompose the 3D-Voronoi cells into points and lines, and generate an initial structural line model based on the points and lines decomposed from the 3D-Voronoi cells.

[0026] 1.6.2 Since adjacent 3D-Voronoi cells in the 3D-Voronoi model are in contact with each other, there are a large number of repeated intersections and lines after the 3D-Voronoi cells are decomposed into points and lines. Therefore, the repeated intersections and lines in the initial structure line model are cleaned up, that is, the repeated points and lines are deleted, and the remaining intersections and lines in the initial structure line model constitute the structure line model.

[0027] 1.7 The structural line model is transformed into a structural body model, and the open-cell foam material matrix is ​​obtained from the structural body model by:

[0028] 1.7.1 Initialize the diameter d of the structure line in the structure line model to any positive number, so that the structure line in the structure line model is transformed from a line generator to a structure body model.

[0029] 1.7.2 Use the modeling software Rhino (version 6.0 and above) to calculate the volume V of the structural model.

[0030] 1.7.3 Calculate the theoretical volume V of the open-cell foam matrix using formula (2): n :

[0031] V n =V0×ε (2)

[0032] Where ε represents the relative density of the open-cell foam material matrix, which is equal to the relative density of the open-cell foam material in the open-cell foam-based interpenetrating composite material model.

[0033] 1.7.4 Compare the volume V of the structural model with the theoretical volume V of the open-cell foam matrix. n For comparison, if V n -V>0.5mm 3 , indicating that the volume V of the structural model is small, smaller than the theoretical volume V n , it is necessary to increase the diameter d of the structure line in the structure line model, go to 1.7.1; if V n -V<-0.5mm 3 , indicating that the volume V of the structure model is large, and it is necessary to reduce the diameter d of the structure line in the structure line model, go to 1.7.1; if │V n -V│≤0.5mm 3 , indicating the total volume V of the structural model and the theoretical volume V of the open-cell foam matrix n Approximately equal, at this time, the structural model is the open-cell foam material matrix, turn 1.8.

[0034] 1.8 Construct an initial filling phase model with the same geometry and size as the open-cell foam-based interpenetrating phase composite model.

[0035] 1.9 Place the initial filling phase model at the geometric center of the open-cell foam material matrix, remove the material of the open-cell foam material matrix outside the initial filling phase model, and remove the material of the initial filling phase model in the overlapping part with the open-cell foam material matrix to obtain an open-cell foam-based interpenetrating phase composite material model.

[0036] In the second step, finite element analysis is performed on the open-cell foam-based interpenetrating composite material model 3 constructed in the first step using finite element analysis software (such as ANSYS (version 19.2 and above) or ABAQUS (version 6.14 and above)), the method is:

[0037] 2.1 In order to more realistically reflect the stress condition of the open-cell foam-based interpenetrating composite material model, an upper pressing plate is established at the contact point with the upper surface of the open-cell foam-based interpenetrating composite material model, and a lower pressing plate is established at the contact point with the lower surface of the open-cell foam-based interpenetrating composite material model. The open-cell foam-based interpenetrating composite material model is located at the geometric center between the upper pressing plate and the lower pressing plate. The upper pressing plate and the lower pressing plate are disks with exactly the same geometric dimensions, and the cross-sectional diameter of the upper pressing plate and the lower pressing plate is greater than the cross-sectional diameter of the open-cell foam-based interpenetrating composite material matrix, and there is no special requirement for thickness.

[0038] 2.2 Finite element meshing is performed on the open-cell foam-based interpenetrating composite material model 3 and the upper and lower pressure plates. The open-cell foam-based interpenetrating composite material model 3 adopts tetrahedral meshes, and the upper and lower pressure plates adopt hexahedral meshes. The meshes are evenly distributed on the open-cell foam-based interpenetrating composite material model, the upper and lower pressure plates.

[0039] 2.3 Constrain the motion boundaries of the upper and lower pressing plates, establish a Cartesian coordinate system, and do not allow the upper pressing plate to have displacement in the X and Y directions, nor to rotate in the X, Y, and Z directions. The upper pressing plate is only allowed to move in the Z direction, and the lower pressing plate is not allowed to have displacement or rotation in the X, Y, and Z directions.

[0040] 2.4 The contact between the upper pressure plate and the upper surface of the open-cell foam-based interpenetrating composite material model is defined as surface-to-surface contact, the contact between the lower pressure plate and the lower surface of the open-cell foam-based interpenetrating composite material model is defined as surface-to-surface contact, and the contact between the open-cell foam material and the filling phase material in the open-cell foam-based interpenetrating composite material model is defined as erosion contact.

[0041] 2.5 Determine the materials of the open-cell foam-based interpenetrating composite material model, upper pressure plate, and lower pressure plate according to the application scenario. The materials of the open-cell foam-based interpenetrating composite material model are determined according to the open-cell foam-based interpenetrating composite material required by the application scenario, including the material of the filling phase and the material of the open-cell foam material matrix. The material of the filling phase is a phase change material, preferably paraffin; the material of the open-cell foam material matrix is ​​an open-cell foam metal, preferably open-cell foam copper. The materials of the upper and lower pressure plates are the same, generally high-strength steel, with a strength requirement of more than 600MPa.

[0042] 2.6 The display dynamics analysis step of the finite element analysis software is used to perform finite element analysis on the open-cell foam-based interpenetrating composite material model, the upper pressure plate, and the lower pressure plate, and the mechanical properties characterization parameters of the open-cell foam-based interpenetrating composite material model, including yield strength σ, failure stress Q, elastic modulus E, and energy absorption parameter D, are obtained.

[0043] The third step is to compare the mechanical property characterization parameters of the open-cell foam-based interpenetrating composite material model obtained by the finite element analysis process in the second step, namely, yield strength σ, failure stress Q, elastic modulus E, and energy absorption parameter D, with the mechanical property characterization parameters of the application environment requirements, namely, yield strength σ0, failure stress Q0, elastic modulus E0, and energy absorption parameter D0, to detect whether the mechanical property characterization parameters of the open-cell foam-based interpenetrating composite material model meet the application environment requirements. If you need to detect the mechanical property characterization parameter yield strength σ of the open-cell foam-based interpenetrating composite material model, go to 3.1; if you need to detect the mechanical property characterization parameter failure stress Q of the open-cell foam-based interpenetrating composite material model, go to 3.2; if you need to detect the mechanical property characterization parameter elastic modulus E of the open-cell foam-based interpenetrating composite material model, go to 3.3; if you need to detect the mechanical property characterization parameter energy absorption parameter D of the open-cell foam-based interpenetrating composite material model, go to 3.4;

[0044] 3.1 If σ≥σ0, it means that the yield strength of the open-cell foam-based interpenetrating composite material model meets the application requirements, and the conclusion is drawn that the yield strength of the open-cell foam-based interpenetrating composite material model is qualified; if σ<σ0, it means that the yield strength of the open-cell foam-based interpenetrating composite material model does not meet the application requirements, and the conclusion is drawn that the yield strength of the open-cell foam-based interpenetrating composite material model is unqualified. If you need to continue to detect whether the failure stress Q of the open-cell foam-based interpenetrating composite material meets the application requirements, go to 3.2; if you need to continue to detect whether the elastic modulus E of the open-cell foam-based interpenetrating composite material meets the application requirements, go to 3.3; if you need to continue to detect whether the energy absorption parameter D of the open-cell foam-based interpenetrating composite material meets the application requirements, go to 3.4; if you need to end the detection, go to 3.5;

[0045] 3.2 If Q ≥ Q0, it means that the failure stress of the open-cell foam-based interpenetrating composite material model meets the application requirements, and the conclusion is drawn that the failure stress of the open-cell foam-based interpenetrating composite material model is qualified; if Q < Q0, it means that the failure stress of the open-cell foam-based interpenetrating composite material model does not meet the application requirements, and the conclusion is drawn that the failure stress of the open-cell foam-based interpenetrating composite material model is unqualified. If you need to continue to test whether the elastic modulus E of the open-cell foam-based interpenetrating composite material meets the application requirements, go to 3.3; if you need to continue to test whether the energy absorption parameter D of the open-cell foam-based interpenetrating composite material meets the application requirements, go to 3.4; if you need to end the test, go to 3.5;

[0046] 3.3 If E ≥ E0, it means that the elastic modulus of the open-cell foam-based interpenetrating composite material model meets the application requirements, and the conclusion is drawn that the elastic modulus of the open-cell foam-based interpenetrating composite material model is qualified; if E < E0, it means that the elastic modulus of the open-cell foam-based interpenetrating composite material model does not meet the application requirements, and the conclusion is drawn that the elastic modulus of the open-cell foam-based interpenetrating composite material model is unqualified. If you need to continue to test whether the energy absorption parameter D of the open-cell foam-based interpenetrating composite material meets the application requirements, go to 3.4; if you need to end the test, go to 3.5;

[0047] 3.4 If D≥D0, it means that the energy absorption parameters of the open-cell foam-based interpenetrating composite material model meet the application requirements, and it is concluded that the energy absorption parameters of the open-cell foam-based interpenetrating composite material model are qualified; if D<D0, it means that the energy absorption parameters of the open-cell foam-based interpenetrating composite material model do not meet the application requirements, and it is concluded that the energy absorption parameters of the open-cell foam-based interpenetrating composite material model are unqualified. Go to 3.5;

[0048] 3.5 The test is completed and the test results are output.

[0049] The mechanical property test results of the open-cell foam-based interpenetrating phase composite materials provide guidance for further work of designers. If the test results meet the application requirements, it means that the design of the open-cell foam-based interpenetrating phase composite materials according to the open-cell foam-based interpenetrating phase composite material model is reasonable and can be put into production; if the test results do not meet the application requirements, it means that the design of the open-cell foam-based interpenetrating phase composite materials according to the open-cell foam-based interpenetrating phase composite material model is unreasonable and needs to be improved. According to the mechanical property characterization parameters of the open-cell foam-based interpenetrating phase composite materials given by the test results, the reason why the open-cell foam-based interpenetrating phase composite materials designed according to the open-cell foam-based interpenetrating phase composite material model does not meet the application environment requirements should be determined, and the open-cell foam-based interpenetrating phase composite materials should be further designed. After the design is completed, the mechanical property test of the present invention is performed.

[0050] Compared with the prior art, the present invention can achieve the following beneficial effects:

[0051] (1) In step 1.1 of the present invention, a model is built for the open-cell foam-based interpenetrating phase composite material to be tested. During the test, a model of the open-cell foam-based interpenetrating phase composite material consistent with the application scenario is used. There is no need to actually prepare the open-cell foam-based interpenetrating phase composite material, nor is there a need for special experimental equipment and experimental personnel with professional skills. On the one hand, time and labor costs can be saved to a great extent, and the detection efficiency can be improved. On the other hand, the test is not affected by factors such as the preparation process of the open-cell foam-based interpenetrating phase composite material, the experimental equipment and experimental operation errors, and the environment, thereby reducing the test error.

[0052] (2) The open-cell foam-based interpenetrating phase composite material model established by the method for testing the mechanical properties of open-cell foam-based interpenetrating phase composite materials provided by the present invention comprehensively considers the accuracy of the open-cell foam-based interpenetrating phase composite material compared with the real material in steps 1.6 and 1.7 (for example, the structural model generated by the structural line model is basically consistent with the required real material). The mechanical properties of the open-cell foam-based interpenetrating phase composite material are tested by the present invention, and the results obtained are more accurate than the mechanical properties test results obtained by finite element analysis through a simplified model. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 It is the overall flow chart of the present invention;

[0054] Figure 2 This is a flow chart of the first step of establishing an open-cell foam-based interpenetrating phase composite material model of the present invention;

[0055] Figure 3 It is the model diagram constructed in the first step of the present invention, Figure 3 (a) is an open-cell foam material matrix constructed in step 1.7 of the present invention, Figure 3(b) is the open-cell foam-based interpenetrating composite material model constructed in step 1.9 of the present invention;

[0056] Figure 4 It is a schematic diagram of the finite element calculation in the second step of the present invention;

[0057] Figure 5 It is a comparison chart of mechanical property characterization parameters obtained by using the present invention to test the mechanical properties of open-cell foam-based interpenetrating phase composite materials and mechanical property characterization parameters obtained by the method of testing the mechanical properties of open-cell foam-based interpenetrating phase composite materials through experiments as described in the background art. The abscissa represents engineering strain and the ordinate represents engineering stress. DETAILED DESCRIPTION

[0058] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0059] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0060] The embodiment of the present invention discloses a method for testing the mechanical properties of an open-cell foam-based interpenetrating phase composite material. The overall process is as follows: Figure 1 shown.

[0061] The first step is to establish an open-cell foam-based interpenetrating composite material model. The detailed modeling process of the open-cell foam-based interpenetrating composite material model is as follows: Figure 2 As shown:

[0062] 1.1 According to the application scenario (such as protection of engines and their key components, power systems, electronic equipment, etc.), the shape and size of the open-cell foam-based interpenetrating composite material model are determined. The maximum area of ​​the open-cell foam-based interpenetrating composite material model is greater than or equal to the area of ​​the maximum surface of the protected electronic components. Let the volume of the open-cell foam-based interpenetrating composite material model determined according to the application scenario be V m =785.39mm 3 .

[0063] 1.2 According to the open-cell foam-based interpenetrating composite material model, the volume of the random porous model is determined as V0 and the average number of pores N of the random porous model, and seed points are randomly arranged in the random porous model. The method is:

[0064] The geometric shape of the random porous model is determined as a cuboid, and the volume of the random porous model is defined as V0. The random porous model is required to fully accommodate at least two open-cell foam-based interpenetrating composite material models determined according to the application scenario, that is, V0≥2V m , V0=1571mm 3 The average number of open pores per inch (ppi) of the open-cell foam matrix is ​​determined according to the application scenario (ppi is 30 in the embodiment), and the average number of pores in the random porous model N=2589 is determined by formula (1):

[0065]

[0066] 1.3 Determine the number of seed points M of the 3D-Voronoi model by the average number of holes N in the random porous model, that is, set M=N=2589. (The 3D-Voronoi model is a 3D discretization method based on the Voronoi diagram. It divides the three-dimensional space into a series of polyhedral units, each of which contains a discrete point (called a "seed point"). Foam materials with different structures can be generated by controlling the number of seed points M, the minimum distance between seed points, and the wall thickness of the polyhedral unit. In this example, the foam material is generated by controlling the number of seed points M=2589.

[0067] 1.4 Randomly arrange M seed points in the random porous model to fill the entire random porous model.

[0068] 1.5 A 3D-Voronoi model is established based on randomly arranged seed points in the random porous model, and a 3D-Voronoi cell is generated from the 3D-Voronoi model.

[0069] There is a space near the randomly distributed seed points in the random porous model, which is called the Voronoi unit. The distance from any point A in the Voronoi unit (any point except the seed point) to the seed point Q in the Voronoi unit is smaller than the distance from point A to other seed points in the space (other seed points except point Q), that is, each Voronoi unit only encloses one seed point. A 3D-Voronoi model is constructed by all Voronoi units in the random porous model. Through the 3D-Voronoi model, a series of 3D-Voronoi cells can be obtained. Each 3D-Voronoi cell corresponds to a seed point in the random porous model and has different geometric shapes and sizes.

[0070] 1.6 Extract the points and lines of the 3D-Voronoi cells and generate the structural line model by:

[0071] 1.6.1 Decompose the 3D-Voronoi cells into points and lines, and generate an initial structural line model based on the points and lines decomposed from the 3D-Voronoi cells.

[0072] 1.6.2 Since adjacent 3D-Voronoi cells in the 3D-Voronoi model are in contact with each other, there are a large number of repeated intersections and lines after the 3D-Voronoi cells are decomposed into points and lines. Therefore, the repeated intersections and lines in the initial structure line model are cleaned up, that is, the repeated points and lines are deleted, and the remaining intersections and lines in the initial structure line model constitute the structure line model.

[0073] 1.7 The structural line model is transformed into a structural body model, and the open-cell foam material matrix is ​​obtained from the structural body model by:

[0074] 1.7.1 Initialize the diameter d of the structure line in the structure line model to any positive number, take d = 0.1mm, so that the structure line in the structure line model is transformed from a line generating body, and the structure line model is transformed into a structure body model.

[0075] 1.7.2 Use the modeling software Rhino (version 6.0) to calculate the volume of the structure model V = 43.67 mm 3 .

[0076] 1.7.3 Calculate the theoretical volume V of the open-cell foam matrix using formula (2): n =43.988mm 3 :

[0077] V n =V0×ε (4)

[0078] Where ε represents the relative density of the open-cell foam material matrix, which is equal to the relative density of the open-cell foam material in the open-cell foam-based interpenetrating composite material model, which is 0.028.

[0079] 1.7.4 Compare the volume V of the structural model with the theoretical volume V of the open-cell foam matrix. n For comparison, if V n -V>0.5mm 3 , indicating that the volume V of the structural model is small, smaller than the theoretical volume V n , it is necessary to increase the diameter d of the structure line in the structure line model, go to 1.7.1; if V n -V<-0.5mm 3 , indicating that the volume V of the structure model is large, and it is necessary to reduce the diameter d of the structure line in the structure line model, go to 1.7.1; if │Vn -V│≤0.5mm 3 , indicating the total volume V of the structural model and the theoretical volume V of the open-cell foam matrix n are approximately equal, in this case, the structural model is an open-cell foam material matrix. n -V=43.988-43.67=0.318(mm 3 )≤0.5mm 3 , at this time, the structural model is the open-cell foam material matrix, such as Figure 3 As shown in (a), the geometric shape of the open-cell foam matrix is ​​a rectangular parallelepiped, and the open-cell foam matrix has an open porosity greater than 90%, which can fill the phase change material into the pores. Under impact load, the cells of the open-cell foam matrix absorb energy during deformation and collapse, and have a certain strength, turning 1.8.

[0080] 1.8 Construct an initial filling phase model with the same geometry and size as the open-cell foam-based interpenetrating phase composite model.

[0081] 1.9 Place the initial filling phase model at the geometric center of the open-cell foam material matrix, remove the material of the open-cell foam material matrix outside the initial filling phase model, and remove the material of the initial filling phase model in the overlapped part of the initial filling phase model and the open-cell foam material matrix to obtain an open-cell foam-based interpenetrating phase composite material model. Figure 3 As shown in (b), the open-cell foam-based interpenetrating composite material model 3 is composed of a filling phase model 31 (the difference from the initial filling phase model is that the material that overlaps with the open-cell foam material matrix in the initial filling phase model is removed) filled in an open-cell foam material matrix 32. The filling phase model 31 and the open-cell foam material matrix 32 are two separate parts in space, and they run through the entire open-cell foam-based interpenetrating composite material model 3. Since the components of the open-cell foam-based interpenetrating composite material are interconnected in three-dimensional space and entangled in all directions, the interface volume ratio is quite high, and the open-cell foam-based interpenetrating composite material model 3 can meet certain mechanical properties.

[0082] In the second step, finite element analysis is performed on the open-cell foam-based interpenetrating composite material model 3 constructed in the first step using finite element analysis software (ANSYS 19.2 version is used in this embodiment), and the method is:

[0083] 2.1 In order to more realistically reflect the stress condition of the open-cell foam-based interpenetrating composite material model 3, an upper pressure plate 1 is established at the contact point with the upper surface of the open-cell foam-based interpenetrating composite material model 3, and a lower pressure plate 2 is established at the contact point with the lower surface of the open-cell foam-based interpenetrating composite material model 3, as shown in FIG. Figure 4As shown, the open-cell foam-based interpenetrating composite material model 3 is located at the geometric center between the upper pressing plate 1 and the lower pressing plate 2. The upper pressing plate 1 and the lower pressing plate 2 are disks with exactly the same geometric dimensions, and the cross-sectional diameter of the upper pressing plate 1 and the lower pressing plate 2 is greater than the cross-sectional diameter of the open-cell foam-based interpenetrating composite material matrix, and there is no special requirement for the thickness.

[0084] 2.2 Finite element mesh division is performed on the open-cell foam-based interpenetrating composite material model 3 and the upper pressure plate 1 and the lower pressure plate 2. The open-cell foam-based interpenetrating composite material model 3 adopts tetrahedral mesh, and the upper pressure plate 1 and the lower pressure plate 2 adopt hexahedral mesh. The meshes are evenly distributed on the open-cell foam-based interpenetrating composite material model 3, the upper pressure plate 1 and the lower pressure plate 2.

[0085] 2.3 Define the motion boundaries of the upper platen 1 and the lower platen 2, and establish a Cartesian coordinate system such as Figure 4 The upper pressing plate 1 is not allowed to have displacement in the X and Y directions, nor is it allowed to rotate in the X, Y and Z directions. The upper pressing plate 1 is only allowed to move along the Z direction, and the lower pressing plate 2 is not allowed to have displacement or rotation in the X, Y and Z directions.

[0086] 2.4 The contact between the upper pressing plate 1 and the upper surface of the open-cell foam-based interpenetrating composite material model 3 is defined as surface-to-surface contact, the contact between the lower pressing plate 2 and the lower surface of the open-cell foam-based interpenetrating composite material model 3 is defined as surface-to-surface contact, and the contact between the open-cell foam material and the filling phase material in the open-cell foam-based interpenetrating composite material model 3 is defined as erosion contact.

[0087] 2.5 Determine the materials of the open-cell foam-based interpenetrating composite material model 3, the upper pressing plate 1, and the lower pressing plate 2 according to the application scenario. The materials of the open-cell foam-based interpenetrating composite material model 3 are determined according to the open-cell foam-based interpenetrating composite material required by the application scenario, including the material of the filling phase and the material of the open-cell foam material matrix. In the embodiment, the material of the filling phase is paraffin; the material of the open-cell foam material matrix is ​​open-cell foam copper. The materials of the upper pressing plate 1 and the lower pressing plate 2 are the same. In the embodiment, high-strength steel is used with a strength of 650MPa.

[0088] 2.6 The display dynamics analysis step of the finite element analysis software is used to perform finite element analysis on the open-cell foam-based interpenetrating composite material model 3, the upper pressure plate 1, and the lower pressure plate 2, and the mechanical properties characterization parameters of the open-cell foam-based interpenetrating composite material model 3, including yield strength σ, failure stress Q, elastic modulus E, and energy absorption parameter D, are obtained.

[0089] The third step is to compare the mechanical property characterization parameters of the open-cell foam-based interpenetrating composite material model 3 obtained by the finite element analysis process in the second step, namely, yield strength σ, failure stress Q, elastic modulus E, and energy absorption parameter D, with the mechanical property characterization parameters of the application environment requirements, namely, yield strength σ0, failure stress Q0, elastic modulus E0, and energy absorption parameter D0, to detect whether the mechanical property characterization parameters of the open-cell foam-based interpenetrating composite material model meet the application environment requirements. If you need to detect the mechanical property characterization parameter yield strength σ of the open-cell foam-based interpenetrating composite material model, go to 3.1; if you need to detect the mechanical property characterization parameter failure stress Q of the open-cell foam-based interpenetrating composite material model, go to 3.2; if you need to detect the mechanical property characterization parameter elastic modulus E of the open-cell foam-based interpenetrating composite material model, go to 3.3; if you need to detect the mechanical property characterization parameter energy absorption parameter D of the open-cell foam-based interpenetrating composite material model, go to 3.4;

[0090] 3.1 If σ≥σ0, it means that the yield strength of the open-cell foam-based interpenetrating composite material model meets the application requirements and the yield strength of the open-cell foam-based interpenetrating composite material model is qualified; if σ<σ0, it means that the yield strength of the open-cell foam-based interpenetrating composite material model does not meet the application requirements and the yield strength of the open-cell foam-based interpenetrating composite material model is unqualified. If you need to continue to detect whether the failure stress Q of the open-cell foam-based interpenetrating composite material meets the application requirements, go to 3.2; if you need to continue to detect whether the elastic modulus E of the open-cell foam-based interpenetrating composite material meets the application requirements, go to 3.3; if you need to continue to detect whether the energy absorption parameter D of the open-cell foam-based interpenetrating composite material meets the application requirements, go to 3.4; if you need to end the test, go to 3.5;

[0091] 3.2 If Q ≥ Q0, it means that the failure stress of the open-cell foam-based interpenetrating composite material model meets the application requirements, and the failure stress of the open-cell foam-based interpenetrating composite material model is qualified; if Q < Q0, it means that the failure stress of the open-cell foam-based interpenetrating composite material model does not meet the application requirements, and the failure stress of the open-cell foam-based interpenetrating composite material model is unqualified. If you need to continue to test whether the elastic modulus E of the open-cell foam-based interpenetrating composite material meets the application requirements, go to 3.3; if you need to continue to test whether the energy absorption parameter D of the open-cell foam-based interpenetrating composite material meets the application requirements, go to 3.4; if you need to end the test, go to 3.5;

[0092] 3.3 If E ≥ E0, it means that the elastic modulus of the open-cell foam-based interpenetrating composite material model meets the application requirements and the elastic modulus of the open-cell foam-based interpenetrating composite material model is qualified; if E < E0, it means that the elastic modulus of the open-cell foam-based interpenetrating composite material model does not meet the application requirements and the elastic modulus of the open-cell foam-based interpenetrating composite material model is unqualified. If you need to continue to test whether the energy absorption parameter D of the open-cell foam-based interpenetrating composite material meets the application requirements, go to 3.4; if you need to end the test, go to 3.5;

[0093] 3.4 If D≥D0, it means that the energy absorption parameters of the open-cell foam-based interpenetrating composite material model meet the application requirements, and the energy absorption parameters of the open-cell foam-based interpenetrating composite material model are considered qualified; if D<D0, it means that the energy absorption parameters of the open-cell foam-based interpenetrating composite material model do not meet the application requirements, and the energy absorption parameters of the open-cell foam-based interpenetrating composite material model are considered unqualified. End the test and go to 3.5;

[0094] 3.5 The test is completed and the test results are output.

[0095] In order to verify that the present invention has accuracy and high detection efficiency, the mechanical properties of the open-cell foam-based interpenetrating phase composite material described in Example 1 of the present invention are experimentally tested, and the experimental test results are compared with the test results of the present invention. The methods for detecting the mechanical property characterization parameters yield strength, failure stress, elastic modulus, and energy absorption parameters in the third step are basically the same, and the effect can be explained by taking the yield strength and energy absorption parameters as examples. Through step 2.6, the open-cell foam-based interpenetrating phase composite material of the embodiment is obtained at a strain rate of 1700s -1 The yield strength σ under the test is 12.2MPa, the mechanical property index of yield strength σ0 is 10.0MPa, σ≥σ0, and the test shows that the yield strength of the open-cell foam-based interpenetrating phase composite material model is qualified.

[0096] The strain rate was set to 1700 s -1 The results of the experiment and the present invention are plotted together on Figure 5 middle, Figure 5The black curve in the figure represents the test result of the present invention, and the red curve represents the test result of the experimental method. The horizontal axis represents the engineering strain, and the vertical axis represents the engineering stress. When operating the experimental equipment, due to improper clamping of the experimental device, there is a large system error, resulting in a difference between the red curve and the black curve before the engineering strain is 0.15. The mechanical performance index that the present invention mainly focuses on is the yield strength (that is, the corresponding engineering stress when the engineering strain is 0.15). It can be seen that the accuracy of the present invention is better. In addition, by comparing the energy absorption parameters of the test results of the present invention with those of the test results of the experimental method (that is, the area enclosed by the engineering stress and the engineering strain when the engineering strain is in the range of 0-0.3 represents the energy absorption parameter), it can be seen that the test results of the present invention are approximately equal to the test results of the experimental method, and the accuracy is good. Therefore, the present invention is used to experimentally test the mechanical properties of open-cell foam-based interpenetrating phase composite materials, and the accuracy of the test results can reach the accuracy of the implementation method. The comparison between the test results of failure stress and elastic modulus and the experimental results is as follows. Figure 5 Basically the same, no further elaboration.

[0097] When the mechanical properties of the open-cell foam-based interpenetrating phase composite material are tested by the experimental method, it takes 8 hours from material preparation to the final completion of the experiment, and 3 open-cell foam-based interpenetrating phase composite material wastes appear in the preparation process. When operating the experimental equipment, there is a large system error due to improper clamping of the experimental device. However, by adopting the present invention, it only takes 1 hour to complete the entire process, and there is no waste, which greatly improves the test efficiency and saves costs.

[0098] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0099] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for testing the mechanical properties of an open-cell foam-based interpenetrating phase composite material, characterized by comprising the following steps: The first step is to establish an open-cell foam-based interpenetrating phase composite model by: 1.1 The shape and size of the open-cell foam-based interpenetrating composite material model are determined according to the application scenario. The maximum area of ​​the open-cell foam-based interpenetrating composite material model is greater than or equal to the area of ​​the maximum surface of the protected electronic component. The volume of the open-cell foam-based interpenetrating composite material model determined according to the application scenario is V m ; 1.2 According to the open-cell foam-based interpenetrating phase composite material model, the volume of the random porous model is determined as V0 and the average number of pores N of the random porous model, and seed points are randomly arranged in the random porous model; 1.3 Determine the number of seed points M of the 3D-Voronoi model by the average number of holes N in the random porous model, that is, let M = N; the 3D-Voronoi model divides the three-dimensional space into a series of polyhedral units, each of which contains a discrete point, namely the "seed point", and generates foam materials with different structures by controlling the number of seed points M, the minimum distance between seed points, and the wall thickness of the polyhedral unit; 1.4 Randomly arrange M seed points in the random porous model to fill the entire random porous model; 1.5 A 3D-Voronoi model is established based on the randomly distributed seed points in the random porous model, and a 3D-Voronoi cell is generated from the 3D-Voronoi model; there is a space near the randomly distributed seed points in the random porous model, which is called a Voronoi unit, and each Voronoi unit wraps a seed point; a 3D-Voronoi model is constructed from all Voronoi units in the random porous model, and a series of 3D-Voronoi cells are obtained through the 3D-Voronoi model; each 3D-Voronoi cell corresponds to a seed point in the random porous model and has different geometric shapes and sizes; 1.6 Extract the points and lines of the 3D-Voronoi cells and generate a structural line model; 1.7 The structural line model is transformed into a structural body model, and an open-cell foam material matrix is ​​obtained from the structural body model; 1.8 Construct an initial filling phase model with the same geometry and size as the open-cell foam-based interpenetrating phase composite model; 1.9 The initial filling phase model is placed at the geometric center of the open-cell foam material matrix, and the material of the open-cell foam material matrix outside the initial filling phase model is removed, and the material of the initial filling phase model in the overlapped portion with the open-cell foam material matrix is ​​removed, so as to obtain an open-cell foam-based interpenetrating phase composite material model (3); the open-cell foam-based interpenetrating phase composite material model (3) is composed of the filling phase model (31) filled in the open-cell foam material matrix (32), and the filling phase model (31) and the open-cell foam material matrix (32) are two separate parts in space, and they run through the entire open-cell foam-based interpenetrating phase composite material model (3); the difference between the filling phase model 31 and the initial filling phase model is that the material in the overlapped portion with the open-cell foam material matrix 32 in the initial filling phase model is removed; In the second step, finite element analysis is performed on the open-cell foam-based interpenetrating phase composite material model (3) constructed in the first step using finite element analysis software, the method being: 2.1 An upper pressing plate (1) is established at a position in contact with the upper surface of the open-cell foam-based interpenetrating composite material model (3), and a lower pressing plate (2) is established at a position in contact with the lower surface of the open-cell foam-based interpenetrating composite material model (3), and the open-cell foam-based interpenetrating composite material model (3) is located at the geometric center between the upper pressing plate (1) and the lower pressing plate (2); the upper pressing plate (1) and the lower pressing plate (2) are circular disks with completely identical geometric dimensions, and the cross-sectional diameters of the upper pressing plate (1) and the lower pressing plate (2) are greater than the cross-sectional diameter of the open-cell foam-based interpenetrating composite material matrix; 2.2 Finite element meshing is performed on the open-cell foam-based interpenetrating composite material model (3) and the upper pressing plate (1) and the lower pressing plate (2). The open-cell foam-based interpenetrating composite material model (3) adopts tetrahedral meshes, and the upper pressing plate (1) and the lower pressing plate (2) adopt hexahedral meshes. The meshes are evenly distributed on the open-cell foam-based interpenetrating composite material model (3), the upper pressing plate (1) and the lower pressing plate (2); 2.3 Constrain the motion boundaries of the upper pressing plate (1) and the lower pressing plate (2), establish a Cartesian coordinate system, and do not allow the upper pressing plate (1) to have displacement in the X and Y directions, nor to have rotation in the X, Y and Z directions. The upper pressing plate (1) is only allowed to move along the Z direction, and the lower pressing plate (2) is not allowed to have displacement or rotation in the X, Y and Z directions; 2.4 The contact between the upper pressing plate (1) and the upper surface of the open-cell foam-based interpenetrating composite material model (3) is defined as a surface-to-surface contact, the contact between the lower pressing plate (2) and the lower surface of the open-cell foam-based interpenetrating composite material model (3) is defined as a surface-to-surface contact, and the contact between the open-cell foam material and the filling phase material in the open-cell foam-based interpenetrating composite material model (3) is defined as an erosion contact; 2.5 Determine the materials of the open-cell foam-based interpenetrating composite material model (3), the upper pressing plate (1), and the lower pressing plate (2) according to the application scenario. The materials of the open-cell foam-based interpenetrating composite material model (3) are determined according to the open-cell foam-based interpenetrating composite material required by the application scenario, including the material of the filling phase and the material of the open-cell foam material matrix. The material of the filling phase is a phase change material, and the material of the open-cell foam material matrix is ​​an open-cell foam metal. The materials of the upper pressing plate (1) and the lower pressing plate (2) are the same, and high-strength steel is used; 2.6 The open-cell foam-based interpenetrating composite material model (3), the upper pressing plate (1), and the lower pressing plate (2) are subjected to finite element analysis by using the display dynamics analysis step of the finite element analysis software to obtain the mechanical property characterization parameters of the open-cell foam-based interpenetrating composite material model (3), namely, yield strength σ, failure stress Q, elastic modulus E, and energy absorption parameter D; The third step is to compare the mechanical property characterization parameters of the open-cell foam-based interpenetrating composite material model (3) obtained by the finite element analysis process in the second step, namely, the yield strength σ, failure stress Q, elastic modulus E, and energy absorption parameter D, with the mechanical property characterization parameters of the application environment requirements, namely, the yield strength σ0, failure stress Q0, elastic modulus E0, and energy absorption parameter D0, to detect whether the mechanical property characterization parameters of the open-cell foam-based interpenetrating composite material model meet the application environment requirements; if it is necessary to detect the mechanical property characterization parameter yield strength σ of the open-cell foam-based interpenetrating composite material model, go to 3.1; if it is necessary to detect the mechanical property characterization parameter failure stress Q of the open-cell foam-based interpenetrating composite material model, go to 3.2; if it is necessary to detect the mechanical property characterization parameter elastic modulus E of the open-cell foam-based interpenetrating composite material model, go to 3.3; if it is necessary to detect the mechanical property characterization parameter energy absorption parameter D of the open-cell foam-based interpenetrating composite material model, go to 3.4; 3.1 If σ≥σ0, it means that the yield strength of the open-cell foam-based interpenetrating composite material model meets the application requirements, and the conclusion is drawn that the yield strength of the open-cell foam-based interpenetrating composite material model is qualified; if σ<σ0, it means that the yield strength of the open-cell foam-based interpenetrating composite material model does not meet the application requirements, and the conclusion is drawn that the yield strength of the open-cell foam-based interpenetrating composite material model is unqualified; if it is necessary to continue to detect whether the failure stress Q of the open-cell foam-based interpenetrating composite material meets the application requirements, go to 3.2; if it is necessary to continue to detect whether the elastic modulus E of the open-cell foam-based interpenetrating composite material meets the application requirements, go to 3.3; if it is necessary to continue to detect whether the energy absorption parameter D of the open-cell foam-based interpenetrating composite material meets the application requirements, go to 3.4; if it is necessary to end the detection, go to 3.5; 3.2 If Q ≥ Q0, it means that the failure stress of the open-cell foam-based interpenetrating composite material model meets the application requirements, and it is concluded that the failure stress of the open-cell foam-based interpenetrating composite material model is qualified; If Q<Q0, it means that the failure stress of the open-cell foam-based interpenetrating composite material model does not meet the application requirements, and it is concluded that the failure stress of the open-cell foam-based interpenetrating composite material model is unqualified; if it is necessary to continue to detect whether the elastic modulus E of the open-cell foam-based interpenetrating composite material meets the application requirements, go to 3.3; if it is necessary to continue to detect whether the energy absorption parameter D of the open-cell foam-based interpenetrating composite material meets the application requirements, go to 3.4; if it is necessary to end the detection, go to 3.5; 3.3 If E ≥ E0, it means that the elastic modulus of the open-cell foam-based interpenetrating composite material model meets the application requirements, and it is concluded that the elastic modulus of the open-cell foam-based interpenetrating composite material model is qualified; if E < E0, it means that the elastic modulus of the open-cell foam-based interpenetrating composite material model does not meet the application requirements, and it is concluded that the elastic modulus of the open-cell foam-based interpenetrating composite material model is unqualified; if it is necessary to continue to detect whether the energy absorption parameter D of the open-cell foam-based interpenetrating composite material meets the application requirements, go to 3.4; if it is necessary to end the detection, go to 3.5; 3.4 If D ≥ D0, it means that the energy absorption parameters of the open-cell foam-based interpenetrating composite material model meet the application requirements, and it is concluded that the energy absorption parameters of the open-cell foam-based interpenetrating composite material model are qualified; If D<D0, it means that the energy absorption parameters of the open-cell foam-based interpenetrating composite material model do not meet the application requirements, and it is concluded that the energy absorption parameters of the open-cell foam-based interpenetrating composite material model are unqualified; Turn 3.5; 3.5 The test is completed and the test results are output.

2. A method for detecting mechanical properties of an open-cell foam-based interpenetrating composite material as claimed in claim 1, characterized in that in step 1.2, the volume of the random porous model is determined as V0 and the average number of pores N of the random porous model according to the open-cell foam-based interpenetrating composite material model, and the method of randomly arranging seed points in the random porous model is: the geometric shape of the random porous model is determined as a cuboid, the volume of the random porous model is defined as V0, and V0 ≥ 2V m ; Determine the average number of open cells per inch (ppi) of the open-cell foam matrix according to the application scenario, and determine the average number of cells N of the random porous model by formula (1):

3. A method for testing mechanical properties of an open-cell foam-based interpenetrating phase composite material as claimed in claim 2, characterized in that The ppi is 20-100.

4. A method for testing mechanical properties of an open-cell foam-based interpenetrating phase composite material as claimed in claim 1, characterized in that The method for extracting the points and lines of the 3D-Voronoi cells and generating the structural line model as described in step 1.6 is: 1.6.1 Decompose the 3D-Voronoi cell into points and lines, and generate an initial structural line model based on the points and lines decomposed from the 3D-Voronoi cell; 1.6.2 The repeated intersection points and lines in the initial structural line model are cleaned up, that is, the repeated points and lines are deleted, and the remaining intersection points and lines in the initial structural line model constitute the structural line model.

5. A method for testing mechanical properties of an open-cell foam-based interpenetrating phase composite material as claimed in claim 1, characterized in that The method for converting the structure line model into a structure body model in step 1.7 and obtaining the open-cell foam material matrix from the structure body model is: 1.7.1 Initialize the diameter d of the structure line in the structure line model to any positive number, so that the structure line in the structure line model is transformed from a line generator, and the structure line model is transformed into a structure model; 1.7.2 Use the modeling software Rhino (version 6.0 and above) to calculate the volume V of the structural model; 1.7.3 Calculate the theoretical volume V of the open-cell foam matrix using formula (2): n : In n =V0×ε (1) Where ε represents the relative density of the open-cell foam material matrix, which is equal to the relative density of the open-cell foam material in the open-cell foam-based interpenetrating phase composite material model; 1.7.4 Compare the volume V of the structural model with the theoretical volume V of the open-cell foam matrix. n For comparison, if V n -V>0.5mm 3 , indicating that the volume V of the structural model is small, smaller than the theoretical volume V n , it is necessary to increase the diameter d of the structure line in the structure line model, go to 1.7.1; if V n -V<-0.5mm 3 , indicating that the volume V of the structure model is large, and it is necessary to reduce the diameter d of the structure line in the structure line model, go to 1.7.1; if │V n -V│≤0.5mm 3 , indicating that the total volume V of the structural model is related to the theoretical volume V of the open-cell foam matrix n Approximately equal, at this time, the structural model is the open-cell foam material matrix.

6. A method for testing mechanical properties of an open-cell foam-based interpenetrating phase composite material as claimed in claim 5, characterized in that The modeling software Rhino mentioned in step 1.7.2 requires version 6.0 or above.

7. A method for testing mechanical properties of an open-cell foam-based interpenetrating phase composite material as claimed in claim 1, characterized in that The finite element analysis software described in the second step is ANSYS or ABAQUS, ANSYS requires version 19.2 or above, and ABAQUS requires version 6.14 or above.

8. A method for testing mechanical properties of an open-cell foam-based interpenetrating phase composite material as claimed in claim 1, characterized in that The material of the filling phase in step 2.5 is paraffin; the material of the open-cell foam material matrix is ​​open-cell foam copper; the high-strength steel used in the upper pressing plate (1) and the lower pressing plate (2) is required to have a strength greater than 600 MPa.

Citation Information

Patent Citations

  • Design and optimization method for reflector main body with closed-cell foam structure

    CN114861246A

  • 3D-Voronoi-based real pore foam model construction method

    CN118013781A

Cited By

  • Ship base structure design method based on Voronoi diagram

    CN121341371A